The Prevalence and Etiology of Ankle Injury in Professional Karate Players in Iran - Hamidreza Naserpour; Mona Mirjani (Biyumikānīk-i varzishī)
Objective: The aim of this study was to investigate the etiology of ankle injury and its prevalence among the Iranian professional karate players. Methods: Participants were 390 karate kumite players (Mean±SD of age=24.5±2.8 years; Mean±SD of weight=63.5±1.8 kg) attendant in the competitions for the national team selection. Foot and Ankle Ability Measure (FAAM) questionnaire was used for assessing their information of ankle injury such as history, etiology, received treatments, and its effects on their daily living performance and sports activities. Descriptive statistics (Mean±SD) were used to describe the data, and Pearson correlation test was used to evaluate the relationship between daily living and sports scores obtained from FAAM and those self-reported scores at a signiﬁcance level of P≤0.05. Results: Results was reported that 86% of subjects had a history of ankle injury, and most of them occurred during the competition. The most important reason for ankle injury was sudden rotation of the foot and kicking the opponent. In most cases, subjects had self-treatment and did not visit a physician. Correlation coefficients of daily living and sports scores obtained from FAAM with athletes' self-reported scores were 0.588 and 0.742 (P=0.000), respectively. Conclusion: Regarding the prevalence of ankle injury among karate players, it is recommended that specific proprioceptive and strengthening programs be put on the agenda for coaches and athletes to reduce the risk factors of injury. Due to the athletes’ lack of follow-up for treatment and rehabilitation in most injuries, there is a possibility of re-injury to the ankle; therefore, the recovery process should be performed after injury under the supervision of a physician and returning to training should be done after proper interval. ﻿﻿﻿﻿